HBR guide to designing your retirement. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2023)
"When what you do is inextricably tied to who you are for so much of your life, it can be daunting to think of who you'll be if you slow down-or stop working entirely. You've charted your own career journey, made difficult choices, led teams through times of turmoil, celebrated big wins, and moved on from devastating losses. How do you just stop? What do you do without a purpose and a plan-and a crowded calendar? How do you make this next stage of your life fulfilling and satisfying? While the idea of not working can be simultaneously wonderful and overwhelming, you can figure out what you want the end of your career and your retirement to look like before you submit your resignation. This book won't help you figure out whether or not you can afford to retire, but it will help you figure out what you'd like to do and who you'd like to be. You'll learn how to: Assess your readiness to make a transition; make a plan to slow your pace-or stop completely; experiment with possible future selves; find new ways to apply old skills; communicate your plan to key partners; bridge your old identity to the new one you create; and keep connected to the passions and people that matter"--
Next-Gen Retirement: Post-career life has changed, and it demands a new approach / by Heather C. Vough, Christine D. Bataille, Leisa Sargent, and Mary Dean Lee -- How Retirement Changes Your Identity: and two processes to see you through it : an interview with Teresa Amabile / by Curt Nickisch -- Design a Retirement That Excites You: Broaden your range of possibilities / by Jeff Giesea -- What Surviving Pandemic Lockdowns Can Teach Us About Major Life Changes: Lasting change happens when we go through a three-part cycle / by Herminia Ibarra -- How to Craft a Better Retirement: Use job-crafting to plan a fulfilling retirement / by Rob Baker -- Retire with Purpose: Cultivate new sources of meaning / by John Coleman -- Learn to Get Better at Transitions: Retirement is a big transition, yes. But you still have more ahead of you / by Avivah Wittenberg-Cox -- Plan a Satisfying Retirement: You're still you; you just may apply your old skills in a new encore career / by Rebecca Knight -- How to Figure Out What You Want to Do When You "Grow Up": Whether you're 10, 20, 30, or more years away from retirement / Gorick Ng -- Reeling From a Sudden Job Loss? Here's How to Start Healing : When you had no time to plan / by Silviana Falcon and Kandi Wiens -- How to Become a Coach or Consultant After You Retire: Flexible hours, location independence-and a chance to share what you know / by Dorie Clark -- Are You Ready to Serve on a Board?: Don't let your skills and experience go to waste / by Anthony Hesketh, Jo Sellwood-Taylor, and Sharon Mullen -- The Leader's Guide to Retirement: Plan your off ramp, take your time, and give back / by Marc A. Feigen and Ron Williams -- Deciding on a Drastic Change: Recognize and address bias to make better decisions / by Mark Mortensen -- Emotions Aren't the Enemy of Good Decision-Making: Make better decisions by identifying how you feel now-and how you'd like to feel after you face a major
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Retirement -- Planning; Retirement -- Psychological aspects; Decision making; Decision making; Retirement -- Planning; Retirement -- Psychological aspects